ПРОШЕДШЕЕ – ОБЫЧНОЕ ВРЕМЯ И ДАВНОПРОШЕДШЕЕ ВРЕМЯ В НЕМЕЦКОМ И КАРАКАЛПАКСКОМ ЯЗЫКАХ - Ихласов, У.; Ихласов, И. (SCIENCE and SOCIETY, 2017)
The article deals with the comparative study of the Simple Past and Past Perfect tenses in the German and Karakalpak languages. It is emphasized that the basis of Simple Past is Participle. The author of the article states that the system of tense forms of the verb in German is a product of long historical development.